2015
DOI: 10.3923/ajpsaj.2015.155.164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Protein, Energy and Lysine Intake on Growth Performance and Carcass Characteristics of Growing Japanese Quails

Abstract: The present study was performed to investigate the effect of dietary levels of protein, energy and Lys on growth performance and carcass traits of growing Japanese quails during 1-5 weeks of age. A factorial design 3×2×2 arrangement was performed including three levels of crud protein (CP; 22, 23.5 and 25%), two levels of metabolizable energy (ME; 2900 and 3000 kcal ME kgG 1 ) and two levels of total lysine (Lys; 1.3 and 1.45%). Live Body Weight (LBW) at 3 weeks of age and Body Weight Gain (BWG) during 1-3 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…Shrivastav et al (1994) concluded that laying quail performed well when given 19% dietary protein and 2750 kcal ME/ kg and when early diets contained 24 and 20% CP in the starter and finisher periods, respectively. The protein and energy requirements of grower and layer Japanese quail have been reported under different conditions (Alagawany et al, 2014a,b;Reda et al, 2015;Reda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Shrivastav et al (1994) concluded that laying quail performed well when given 19% dietary protein and 2750 kcal ME/ kg and when early diets contained 24 and 20% CP in the starter and finisher periods, respectively. The protein and energy requirements of grower and layer Japanese quail have been reported under different conditions (Alagawany et al, 2014a,b;Reda et al, 2015;Reda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to Kanyinji and Moonga [ 30 ], the increase in FCR may be a consequence of wastage and its reduction may be related to high fiber content. According to Reda et al [ 31 ], factors influencing the FCR are environmental temperature, genetics, body weight, feed nutrient content, and gender differences due to variation in FI.…”
Section: Discussionmentioning
confidence: 99%
“…Both energy and protein constitute 85% of the total cost of feeding in these projects [3]. AA are the only structural, functional, or ctuculturali, that regulate metabolic pathways in the body [4] , stimulate protein synthesis and fat metabolism, and play an important role in increasing broiler growth [5] , in addition, to their antioxidant role, especially methionine. And lysine, threonine, and arginine improve the gut health of birds through their effect on immune globulin [6] , as these acids enter the formation of mucin, which has a role in promoting digestion and absorption processes by increasing goblet cells [7] .…”
Section: Introductionmentioning
confidence: 99%